Heterozygous versus homozygous phenotype caused by the same MC4R mutation: novel mutation affecting a large consanguineous kindred - Max Drabkin; Ohad S. Birk; Ruth Birk (BMC, 2018)
Abstract Background The hypothalamic G-protein-coupled-receptor melanocortin-4 receptor (MC4R) is a key player in the central circuit regulating energy expenditure and appetite. Heterozygous loss-of-function MC4R mutations are the most common known genetic cause of monogenic human obesity, with more than 200 mutations described to date, affecting 2-3% of the population in various cohorts tested. Homozygous or compound heterozygous MC4R mutations are much less frequent, and only few families have been described in which heterozygotes and homozygotes of the same mutation are found. Methods We performed exome sequencing in a consanguineous Bedouin family with morbid obesity to identify the genetic cause of the disease. Clinical examination and biochemical assays were done to delineate the phenotype. Results We report the frequency of MC4R mutations in the large inbred Bedouin Israeli population. Furthermore, we describe consanguineous inbred Bedouin kindred with multiple individuals that are either homozygous or heterozygous carries of the same novel MC4R mutation (c.124G > T, p.E42*). All family members with the homozygous mutation exhibited morbid early-onset obesity, while heterozygote individuals had either a milder overweight phenotype or no discernable phenotype compared to wild type family members. While elder individuals homozygous or heterozygous for the MC4R mutation had abnormally high triglycerides, cholesterol, glucose and HbA1C levels, most did not. Conclusions MC4R mutation homozygotes exhibited morbid early-onset obesity, while heterozygotes had a significantly milder overweight phenotype. Whereas obesity due to MC4R mutations is evident as of early age - most notably in homozygotes, the metabolic consequences emerge only later in life.